Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Pengguna Jasa Tata Rias Pengantin Jawa “Solo Basahan” (Studi Kasus di Kota DKI Jakarta): Penelitian - Mega Kartika; Sri Widjajanti; Dwi Atmanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
When it comes to Javanese wedding makeup services, customer satisfaction is influenced by both the quality of the service and the pricing. There are indicators that the degree of satisfaction that customers have with the services provided by Solo Basahan is not yet at its highest possible level. The purpose of this research is to determine the extent to which the quality of service and the cost affected the level of satisfaction experienced by customers of the